How do undergraduate medical students use the annotation option of a video feedback system when recording consultations with real patients; a qualitative document analysis - Ellemieke Maria Cornelia Rasenberg; Guus Maria Brand; Bernardus Petrus Thoonen Ellemieke; Bernardus Petrus Aloysius Thoonen (BMC Medical Education, 2025)
Abstract Background Observation during clerkships is challenging for clinical supervisors. Using a video feedback system (VFS) to record consultations with a patient, facilitates asynchronous feedback. Within this system it is also possible to add annotations, linked to a timeline. Learners are facilitated to share both recordings and annotations with others, who can provide feedback at a self-selected moment. Methods A qualitative document analysis on the content of annotations from 23 medical students has been conducted to explore how they use the annotation option in a VFS during their first clerkship. Thematic analysis was chosen as an inductive strategy. Results Thirteen students opted to share their videos for feedback, while ten chose not to. The main themes were “content”, “labeling video fragments” and “responses to shared annotations”. Subthemes within the theme “Content” were ‘Typing’, ‘Empathy’, ‘Directing’ and ‘Communication and communications skills’. Students were critical of themselves, but tempered their feedback by mitigating language. Many students made concise notes to their recordings, without adding questions or interpretations. The provided feedback was carefully phrased and alternatives were formulated. Conclusion Students apply “feedback principles” as they have learned from prior training. Alternatives were carefully constructed. It seems they also assess themselves using short notes similar to items of assessments scales. Their tendency to temper their feedback and not always share the videos with others, may indicate the need for a safe learning environment, as a prerequisite for using a VFS. Considering the diligence in feedback provision and varied topics addressed, the use of a VFS seems to be a good way to provide asynchronous feedback on communication skills during clerkships, offering instructors increased observation opportunities and the chance to facilitate peer feedback.